Efektivitas Intradialytic Cycling terhadap Status Fungsional Fisik dan Psikologis pada Pasien Hemodialisis : Telaah Literatur Sistematis - Katarina Windhi Anggita Sari; Yulia Yulia; Chiyar Edison Sunarya; Agung Waluyo (Universitas Pahlawan Tuanku Tambusai, 2025)
Intradialytic cycling is a form of aerobic exercise performed during hemodialysis sessions. Several studies have investigated its impact on both physical and psychological functional status, utilizing various parameters such as frequency, duration, exercise intensity, and with differing outcomes. The aim of this systematic review is to examine the effects of intradialytic cycling on physical and psychological functional status in patients undergoing hemodialysis.This systematic review was conducted in accordance with the PRISMA guidelines. Literature was sourced from databases including Scopus, ProQuest, SAGE Journals, SpringerLink, Taylor & Francis, and Cochrane, using keywords based on the PICO framework and combined with Boolean operators “AND” and “OR.” Inclusion criteria for the articles were: publication between 2010 and 2025, studies involving hemodialysis patients aged ≥18 years, research designs including randomized controlled trials (RCTs), quasi-experimental studies, and cohort studies, and publications in English. A total of 10 articles were included in the analysis. Intradialytic cycling demonstrated enhancing physical function and reducing depressive symptoms in hemodialysis patients. This non-pharmacological intervention proved to be effective both as a standalone therapy and in combination with other modalities, such as resistance training, music therapy, and cognitive approaches. However, further research is warranted to develop and adapt intradialytic cycling protocols that align with clinical practice settings in Indonesia